2021
DOI: 10.1186/s41065-021-00200-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crucial genes involved in pathogenesis of regional weakening of the aortic wall

Abstract: Background The diameter of the abdominal aortic aneurysm (AAA) is the most commonly used parameter for the prediction of occurrence of AAA rupture. However, the most vulnerable region of the aortic wall may be different from the most dilated region of AAA under pressure. The present study is the first to use weighted gene coexpression network analysis (WGCNA) to detect the coexpressed genes that result in regional weakening of the aortic wall. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our gene expression analysis found MYH11 (scored 0.915 by XGB), ACTA2 (scored 0.9 by XGB), and TPM2 (scored 0.865 by XGB) as highly expressed in cardiovascular tissues and have interconnected PPIs. In comparison, studies have found all three of these genes are coexpressed in vascular smooth muscle cells to weaken the aortic wall 43 and to be markers of pulmonary hypertension 44 . We also analysed these clustered genes in DGIdb, nding MYH11 and ACTA2 are both clinically actionable drug targets, suggesting these highly prioritized genes and their interaction network offer targeted directions of investigation with putative drug targets for BP.…”
Section: Discussionmentioning
confidence: 99%
“…Our gene expression analysis found MYH11 (scored 0.915 by XGB), ACTA2 (scored 0.9 by XGB), and TPM2 (scored 0.865 by XGB) as highly expressed in cardiovascular tissues and have interconnected PPIs. In comparison, studies have found all three of these genes are coexpressed in vascular smooth muscle cells to weaken the aortic wall 43 and to be markers of pulmonary hypertension 44 . We also analysed these clustered genes in DGIdb, nding MYH11 and ACTA2 are both clinically actionable drug targets, suggesting these highly prioritized genes and their interaction network offer targeted directions of investigation with putative drug targets for BP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in animal models of aortic aneurysms, SMC-specific gene downregulation precedes the weakening of the arterial wall [ 69 ] and KLF4 deficiency inhibits aneurysm formation [ 60 ]. Additionally, heterozygous mutations, or differential expression of proteins from the VSMC contractile apparatus, as well as the kinases that regulate their assembly, have been linked to the formation of aneurysms in humans [ 6 , 7 , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Discussionmentioning
confidence: 99%
“…This ability is critical for vessel maturation, remodeling, and injury repair but also increases susceptibility to vascular diseases [ 1 ]. For instance, in aortic aneurysms, weakening of arterial walls results from complex vessel wall remodeling, where VSMC phenotypic modulation plays a central role [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, genome-wide analyses, such as high-throughput sequencing technology and gene chips, have been routinely used to study gene expression patterns [ 13 ]. The analysis of these data has fostered the development of bioinformatics and derived methods such as Weighted Gene Co-Expression Network Analysis (WGCNA) and Receiver Operating Characteristic (ROC) analysis, which can provide valuable information for biomarker discovery of diseases [ 14 16 ]. In this study, we used the gene expression datasets from different populations in different countries to screen out the common differentially expressed genes (DEGs) in peripheral blood cells of patients with or without sepsis.…”
Section: Introductionmentioning
confidence: 99%